2017
DOI: 10.1007/s00221-017-5081-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between attentional systems and episodic memory encoding: the impact of conflict on binding of information

Abstract: Episodic memory (EM) is defined as a long-term memory system that stores information that can be retrieved along with details of the context of the original events (binding). Several studies have shown that manipulation of attention during encoding can impact subsequent memory performance. An influential model of attention distinguishes between three partially independent attentional networks: the alerting, the orienting and the executive or conflict resolution component. To date, the impact of the engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As explained, these two sets of results are commonly obtained from research inspired in two separate theoretical approaches, both differing in the definition and measure of episodic memory. The observation of better memory for congruent objects (Sperduti et al 2017 ) generally comes from research considering episodic memory as a long-term memory effect (several minutes) in which multiple features are bound together, similar to the concept that we use in this paper. Conversely, studies finding better memory for incongruent items tend to not measure episodic memory per se, and instead infer a process of episodic retrieval to explain performance in priming tasks.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…As explained, these two sets of results are commonly obtained from research inspired in two separate theoretical approaches, both differing in the definition and measure of episodic memory. The observation of better memory for congruent objects (Sperduti et al 2017 ) generally comes from research considering episodic memory as a long-term memory effect (several minutes) in which multiple features are bound together, similar to the concept that we use in this paper. Conversely, studies finding better memory for incongruent items tend to not measure episodic memory per se, and instead infer a process of episodic retrieval to explain performance in priming tasks.…”
Section: Discussionmentioning
confidence: 97%
“…As explained, these two sets of results are commonly obtained from research inspired in two separate theoretical approaches, both differing in the definition and measure of episodic memory. The observation of better memory for congruent objects (Sperduti et al 2017) generally comes…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…color, shape, word) into a complex memory unit (Tulving, 2002). It represents a core feature of episodic memory (Meiser et al, 2008;Sperduti et al, 2017). Several previous studies have suggested that the hippocampus and the adjacent medial temporal lobe (MTL) structures play a crucial role in binding memory (Konkel et al, 2008;Mayes et al, 2007;Pertzov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%